A modulação de eficácia da norma tributária em controle de constitucionalidade no Supremo Tribunal Federal - Cavalcante, Mantovanni Colares (2016)
The proposal of this thesis is to demonstrate that the effects attributed by the Supreme Court on judicial review can not be defined without proper bond with the previous steps to the judgment of the legal action; and this modulation, considered the technique to restrict the effects of the declaration of unconstitutionality, or determine that a statement only be valid from the final judgment, from decision or other time as may be fixed, and this effects are more relevant in relation to norm of tax law, because of weakening of judicial review in a special appeal, and the strengthening of abstract judicial review, which is the analysis of tax law without regard to the particular case. As a methodological option, the thesis covers the fields of Constitutional Law, Tax Law and Procedural Law, supported by legal texts and decisions of the Supreme Court, anchored in one of the elements of the Paulo de Barros Carvalho theory of tax law, and its construction within the jurisdiction, and Pontes de Miranda theory of preponderance of loads efficacy, in order to demonstrate that there is a specific efficacy in relation to the court decision, which is to procedural efficacy. From these premises, the thesis contains a defense that modulation is the result of a link between the nature of the legal action and its efficacy from the force generated by procedural technique of kinetic energy. In the end, we present suggestions that the modulation could not be an isolated act in the judgment of Supreme Court, on the constitutionality control, with suggestion's split into three guidelines, to serve as parameters in the use of modulation, from the most rigorous, and through a median suggestion, to arrive at a proposal to set minimum procedural standards